Vehicular communication: a survey. Issue 3 (1st September 2014) - Bhoi, Sourav Kumar; Khilar, Pabitra Mohan
Abstract : Vehicular communication is an important and emerging area of research in the field of vehicular technology. The development of software and hardware in communication systems leads to the generation of new networks. Many researches and projects have been conducted in this upcoming area. Many government projects have been implemented in the USA, Japan and the European Union. The main objective of using this new technology is to create an accident free environment. New architectures, protocols and implementations of vehicular ad‐hoc network (VANET) have been made in recent years to provide Intelligent Transportation Services. In this study, the authors survey the current issues like development, deployment, security challenges and about the current projects running in different countries. They also survey the mobility models and simulators required to implement VANET. They have also reviewed the emerging applications of VANET which provides services to the end users. At last, they have presented future research problems in VANET. The main motive of this survey is to explore the current ideas in vehicular communication.